Ocorrência, susceptibilidade à antifúngicos e fatores de virulência de populações de Candida albicans e outras leveduras oportunista isoladas de ambientes aquáticos de Minas Gerais - Lilia de Cassia Espirito Santo (2014)
Monitoring the quality of recreation and consumption freshwater is important in order to establish the risks for the users of being exposed to the contaminants found in these locations. Coliform bacteria are a group of microorganisms commonly used for evaluating the water quality. Although, in anything countries, other microorganisms also be used as pollution indicators complementarily to that group. This study aimed to evaluate the yeast and coliform bacteria counts in aquatic environments of Minas Gerais, and the p the presence of antifungal resistant or virulence factor producing yeasts. Water samples were collected from the São Luís tank (Caraça Natural Park MG), the Pampulha lake (MG), the Dom Helvécio lake (Rio Doce State Park MG) and the Velhas river (MG). About 10 to 50 ml were filtered through nitrocellulose membranes (0.45 m pore size,) and were then positioned on the surface of the CHROMagar-Candida and agar-mCa media. The yeasts of different morphotypes were counted, purified, and stored. The different morpho-types were counted, purified and stocked at -86ºC. The isolates were grouped into morphophysiological and molecular profiles and at least one of each profile was selected and sequenced. All of them were tested for their sensibility to three antifungal agents and for their ability to produce proteinase and phospholipase. All isolates identified as Candida albicans and those resistant or dose-dependent to the three drugs evaluated were also tested for their adhesion ability. A quantification of total coliforms and Escherichia coli was performed. In the São Luís tank and Dom Helvécio lake samples, the yeast counts did not present a positive correlation with the E. coli ones. Although, in the Pampulha lake and in the Velhas river, there was a positive correlation between the counts. One hundred eighty-one isolates were identified belonging to 52 species, and C. albicans and Meyerozyma guilliermondii were the most frequent ones. Regarding their susceptibility profile, 61.7% were fluconazole resistant or dose-dependent, 92% to itraconazole, and only 7.8% were resistant to amphotericin B. Furthermore, 50 and 37 isolated were capable of producing proteinase and phospholipase, respectively. Regarding their C. albicans isolates, five were resistant to the three drugs tested, eight were resistant to the two drugs and two isolates were dose-dependent and resistant to a drug. Only one isolate of 22 tested was not able to adhere to buccal epithelial cells. The C. albicans isolates were the ones that showed a resistant and dose-dependent profile to the antifungals and were the main virulence factor producers. These results suggest that these yeasts could represent a risk to the health of the user of these aquatic environments.